Intelligent irrigation management in mountainous agriculture in AzerbaijanIntellectual - Aliyev, RAE. Z.H. (JOURNAL OF ADVANCES IN NATURAL SCIENCES, 2017)
: This article examines the current state of soil and water resources, farmland t.ch.i Azerbaijan Republic , the problem of progressive water and wind soil degradation , the need for the organization of agriculture , taking into account the introduction of automated control systems for irrigation using water saving technology and hardware equipment in it, the study of the characteristics and analysis of experience implementing measures to stabilize ecological and drainage system of agriculture in conditions of insufficient moisture areas in the country , as well as basic aspects of development of environmental reclamation approach balanced, rational use of a particular system of crop rotation and crop . taking into account the requirements of economic development and environmental management.